Air Quality in Indoor and Characteristics of Workers with Sick Building Syndrome at Mall (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Sick Building Syndrome (SBS) was a healthproblem that caused by air polution, indoor air quality and a bad ventilation. In around the world,2.7 milions of people were dead because air polution in the room and this air polution source from ventilation (52%), tools in the room (17 %), outside the room (11%), the building material (3%), microorganism (5%) and others (12%). Mall was a public place with a close ventilation so it can influence the air quality and being the risk of SBS.The aim of this research was looking for correlation between air quality in the room and the characteristics of workerswith sick building syndrome (SBS).This research was an analytic with cross sectional design. The population was all of the workerwith 36 sample workers.Data analysis used univariat and bivariat.Result of this research showed the variabelswhich had correlationwith sick building syndrome are humidity, wind velocity, light intensity, age, and gender. The variables that had no correlation with sick building syndrome are temperature, microorganism quantity, duration of work and period of work.